Epigenetic regulation of the extrinsic oncosuppressor PTX3 gene in inflammation and cancer. (3rd July 2017) - Rubino, Marcello; Kunderfranco, Paolo; Basso, Gianluca; Greco, Carolina Magdalen; Pasqualini, Fabio; Serio, Simone; Roncalli, Massimo; Laghi, Luigi; Mantovani, Alberto; Papait, Roberto; Garlanda, Cecilia
ABSTRACT: PTX3 is a component of the humoral arm of innate immunity and an extrinsic oncosuppressor gene taming tumor-promoting inflammation. Here, we show that two enhancers differently regulate PTX3 expression: enhancer 1, located 230 kb upstream of PTX3 promoter, mediated the action of inflammatory transcription factors; and enhancer 2, encompassing PTX3 second exon, was implicated in pre-initiation complex assembly. Polycomb repressive complex 2 silenced these regulatory elements and the promoter in basal condition. Enhancer 1 was epigenetically inactivated in early colorectal cancer (CRC) stages, while the promoter and enhancer 2 showed increasingly DNA methylation during CRC progression from adenomas to stage II and III CRC. Inhibition of DNA methylation rescued PTX3 expression in CRC. Finally, enhancer 1 acquired the binding of STAT3 in stage I CRC, and inhibition of STAT3 phosphorylation restored PTX3 activity and decreased enhancer 1 methylation. Thus, the expression of PTX3 is under the control of two enhancers, which emerge as important fine regulators of PTX3 expression in inflammation and cancer.